Women’s knowledge on the menopausal transition in relation to their socio-economic status - Krzyżanowska, Monika; Górecka, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2021)
Current reports indicate that there is a relationship between women’s socio-economic status (SES) and their level of knowledge on the menopausal transition. The aim of the study was to assess the level of knowledge in pre-menopausal women on the most frequent symptoms accompanying the menopausal transition as well as conventional and nonconventional therapies of alleviating symptoms in relation to women’s SES. The study was conducted among 114 women with the mean age of about 44 (± 2.51) years. A self-prepared questionnaire was used to investigate their SES and level of knowledge on the most common menopausal symptoms and methods of alleviating them. Most of the women (66.7%) were familiar with the most frequent menopausal symptoms. The women associated menopause with hot flashes (41.2%), mood swings (27.2%) and depression (15.8%). The majority of the women (84.2%) were familiar with hormone replacement therapy (HRT) and 43% of them were familiar with alternative therapies (AT). Better-educated women were more likely to take AT in the future while less-educated women intended to take HRT. Place of residence and income did not differentiate whether women intended to use HRT or AT during the menopausal transition. There was no difference in the level of women’s knowledge on HRT in relation to SES. There was an association between the level of knowledge on AT and education as well as place of residence. Better-educated women from medium and large urban centres tended to know unconventional methods of alleviating climacteric symptoms. Education was the most significant predictor of self-assessed level of knowledge on the menopausal transition.